Hegemony in the Shadow of Tradition: Hidden Resistance of the Lio Indigenous Community Against Mosalaki Domination in the Era of Modernization - Martina Ue (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This research analyzes the dynamics of hegemony and resistance in the Lio indigenous community of Ende Regency, East Nusa Tenggara, focusing on the power practices of mosalaki (traditional elites) and the forms of hidden resistance developed by farming communities. Using an ethnographic approach over four months in Keliwumbu Village, this study combines Antonio Gramsci's concept of hegemony with James Scott's theory of hidden transcripts to understand the complexity of power relations in traditional societies experiencing economic transformation. Data were collected through participant observation, in-depth interviews with 18 informants, and document analysis, then analyzed using a thematic approach. Findings indicate that the legitimacy of mosalaki power is constructed through three main pillars: genealogical narratives derived from the myths of Lepe and Mbusu, control over customary land encompassing 70% of agricultural land, and ritual authority positioning them as intermediaries with ata mate (ancestral spirits). Hegemonic practices operate through the pire system (customary prohibitions), mandatory nggua rituals requiring offerings, and control over decision-making as evidenced in the coal-fired power plant construction case. However, farming communities have developed hidden resistance in the form of subtle sabotage, passive non-compliance, gossip and informal criticism, and exit strategies through migration and purchase of alternative land. This resistance operates within the same cultural framework as the hegemony it contests, developing alternative interpretations of